2003
DOI: 10.1002/hbm.10089
|View full text |Cite
|
Sign up to set email alerts
|

Neural systems of second language reading are shaped by native language

Abstract: Reading in a second language (L2) is a complex task that entails an interaction between L2 and the native language (L1). To study the underlying mechanisms, we used functional magnetic resonance imaging (fMRI) to visualize Chinese-English bilinguals' brain activity in phonological processing of logographic Chinese and alphabetic English, two written languages with a sharp contrast in phonology and orthography. In Experiment 1, we found that phonological processing of Chinese characters recruits a neural system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
268
1
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 321 publications
(302 citation statements)
references
References 53 publications
(56 reference statements)
30
268
1
3
Order By: Relevance
“…For Chinese, our results converge with results showing greater involvement of bilateral visual-spatial areas and visual-orthographic areas [Bolger et al, 2005;Tan et al, 2005a]. Previous research has also found greater involvement for Chinese reading in a dorsal posterior region of the left inferior frontal gyrus bordering on the precentral gyrus (BA 6/9) [Bolger et al, 2005;Tan et al, 2003Tan et al, , 2005a. In our study, we observed activation during character reading near this same ''Chinese region,'' at the left dorsal inferior frontal gyrus (BA9).…”
Section: Differences Between Chinese and Englishsupporting
confidence: 90%
See 1 more Smart Citation
“…For Chinese, our results converge with results showing greater involvement of bilateral visual-spatial areas and visual-orthographic areas [Bolger et al, 2005;Tan et al, 2005a]. Previous research has also found greater involvement for Chinese reading in a dorsal posterior region of the left inferior frontal gyrus bordering on the precentral gyrus (BA 6/9) [Bolger et al, 2005;Tan et al, 2003Tan et al, , 2005a. In our study, we observed activation during character reading near this same ''Chinese region,'' at the left dorsal inferior frontal gyrus (BA9).…”
Section: Differences Between Chinese and Englishsupporting
confidence: 90%
“…Among the common neural mechanisms, the left temporo-occipital cortex and left inferior parietal lobule (IPL) are involved in both languages for orthographic analysis and conversion between orthography and phonology/semantics, respectively [Bolger et al, 2005;Booth et al, 2006;Tan et al, 2003]. Among the distinctive mechanisms, right temporo-occipital cortex and bilateral superior parietal lobules are more involved in Chinese than English, presumably due to the complex holistic visual-spatial analysis required by Chinese characters [Cao et al, 2010;Tan et al, 2005a].…”
Section: Introductionmentioning
confidence: 99%
“…Our motor memory hypothesis is supported by recent neuroimaging studies that found that written Chinese character recognition is critically mediated by the posterior portion of the left middle frontal gyrus, a region just anterior to the premotor cortex (24,33,34). In addition, functional connectivity analyses of neural pathways involved in language processing indicated that reading in Chinese recruits a neural circuit linking Broca's area in the prefrontal cortex and the supplementary motor area, whereas reading in alphabetic (Western) scripts recruits a neural circuit connecting Broca's area and Wernicke's area (35).…”
Section: Discussionsupporting
confidence: 65%
“…For example, the strong involvement of visuopremotor association in NCS may be related to the experience of reading Chinese characters (15,28). A Chinese character is composed of strokes and subcharacters that are packed into a square configuration, possessing a high, nonlinear visual complexity.…”
Section: Discussionmentioning
confidence: 99%